Strategic Self-Regulation in Groups: Collective Implementation Intentions Help Cooperate When Cooperation Is Called for - Thürmer, J. Lukas; Wieber, Frank; Gollwitzer, Peter M. (Frontiers in Psychology, 2020)
Groups need contributions that are personally costly to their members. Such cooperation is only adaptive when others cooperate as well, since unconditional cooperation may incur high costs to the individual. We argue that individuals can use We-if-then plans (collective implementation intentions; cIIs) to regulate their group-directed behavior strategically, helping them to cooperate selectively with group members in the situation planned for. In line with this prediction, a cII to consider group earnings increased cooperative decisions in a prisoner’s dilemma game (PDG) when playing against another group member but not when playing against a stranger (i.e., non-group member). Moreover, cIIs to cooperate in the PDG did not increase cooperation in a structurally similar investment game that participants had not planned for. We discuss the role of collective planning in solving social dilemmas.